Challenges in Cybercrime Prevention and Legal Frameworks in India: An Analytical Study (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The rise of cybercrime has been a major problem for countries, businesses, and people all around the world. The purpose of this study is to shed light on the difficulties in enforcing laws against cybercrime in India and to highlight the critical need for such a framework in order to stem the tide of this rapidly expanding threat. There has been an upsurge in cybercrime in India in recent years. The fact that it has such a detrimental effect on people's social and economic life makes it a very worrying issue. Data from cybercrime cases prosecuted in India's most susceptible states and cities under the IT Act and the Indian Penal Code formed the basis of our study. In addition, we have examined the data of cybercrime instances perpetrated by individuals of varying ages. In addition to outlining the many reasons for cybercrime and the crimes themselves, this article also provides crucial recommendations on how to reduce cybercrime. Both the investigation and punishment of cybercriminals and the general deterrent against cybercrimes are weakened by these obstacles. To tackle the unique problems posed by cybercrime in India, this study acknowledges the need of a thorough legislative framework and suggests important components that should be included in the laws.